2019
DOI: 10.1002/iub.2162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of consecutive rare codons on the recombinant production of human proteins in Escherichia coli

Abstract: In Escherichia coli the expression of heterologous genes for the production of recombinant proteins can be challenging due to the codon bias of different organisms. The rare codons AGG and AGA are amongst the rarest in E. coli. In this work, by using the human gene RioK2 as case study, we found that the presence of consecutive AGG-AGA led to a premature stop, which may be caused by an event of -1 frameshift. We found that translational problems caused by consecutive AGG-AGA are sequence dependent, in particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Since the only difference between the native phaB and phaB _L are two nucleotides (138-CAG and 130-CTG, respectively) and the same two nucleotides were altered to 138-CAA in phaB -opt ( Supplementary Figure 5 ) it can be assumed that the deleterious effect stems from translational complications in this region. Correddu et al (2019) found that co-occurrence of certain amino acid codons in E. coli led to a premature stop in the protein chain potentially through a frameshift. Similar effects could be at play here.…”
Section: Discussionmentioning
confidence: 99%
“…Since the only difference between the native phaB and phaB _L are two nucleotides (138-CAG and 130-CTG, respectively) and the same two nucleotides were altered to 138-CAA in phaB -opt ( Supplementary Figure 5 ) it can be assumed that the deleterious effect stems from translational complications in this region. Correddu et al (2019) found that co-occurrence of certain amino acid codons in E. coli led to a premature stop in the protein chain potentially through a frameshift. Similar effects could be at play here.…”
Section: Discussionmentioning
confidence: 99%
“…Persentase kandungan GC dari gen hasil optimasi meningkat menjadi 56,57% dan berada dalam kisaran persentase ideal yaitu 30-70% (GenScript, 2019). Correddu et al, (2019) melaporkan translasi yang disebabkan oleh kodon arginin langka (AGG-AGA) pada E. coli, menghasilkan produksi protein RioK2 terpotong. Penggantian kodon langka AGG-AGA dengan kodon arginine CGC-CGT yang dikenali oleh E. coli sebagai inang mencegah produksi protein terpotong.…”
Section: Optimasi Gen Penyandi Lon-like Proteaseunclassified
“…Recombinant DNA technology has made it possible to produce bulk quantities of enzymes and proteins of pharmaceutical importance in E. coli and Bacillus species. Genetically modified bacterial strains with disrupted native protease and RNase enzymes, preferred tRNA genes and genome having lysogenically introduced bacteriophage T7 RNA polymerase gene are often used as a tool for recombinant protein production (Gopal and Kumar, 2013;Correddu et al, 2020;Duarte et al, 2020;Doozandeh-Juibari et al, 2020). Pyrococcus abyssi is an archaeon that grows under stringent conditions with optimum growth temperature 96°C, under anaerobic high pressure conditions (Erauso et al, 1993), its genome has been analysed (Cohen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%